Naïve Consumers and Financial Mistakes - Florian Exler; Alexander Hansak (ZBW - Leibniz Information Centre for Economics, 2021)
Financial contracts are complicated and consumers often do not grasp them in their entirety. This may lead to financial mistakes. We develop a quantitative theory of unsecured credit and equilibrium default in a market with sophisticated and näive borrowers who sometimes misunderstand their contracts and make financial mistakes. Näives are more prone to mistakes without internalizing this fact. When signing debt contracts, we allow agents to trade off interest rates for penalty fees. These fees make financial mistakes costly. Näives choose inefficiently high penalty fees and cross-subsidize interest rates for sophisticates. We use this framework to analyze two unexplored features of the CARD act: clearer language requirements and a limit on penalty fees in financial contracts. Clearer contract terms lead to fewer financial mistakes by everyone, while limiting fees constrains mostly näive borrowers. Both policies reduce financial mistakes and increase the welfare of näive borrowers. The effects on sophisticates differ: clearer language and fewer mistakes benefit sophisticates too. However, limiting fees reduces the cross-subsidization sophisticates receive in equilibrium and consequently makes them worse off.
Keywords: E21; E43; G18; G41; G51; K12; 330; Consumer Credit; Nä iveté; Financial Mistakes; Bankruptcy; CARDAct; Cross-Subsidization